La Generación de Residuos en la Parroquia Carigán de la Ciudad de Loja y su incidencia en la Calidad de vida de la Población, Periodo Enero-Junio 2016 - Quizhpe Camacho, Diana Carolina (2016)
This thesis entitled "The generation of waste in the Carigán parish of the city of Loja and its impact on the quality of life of the population, January-June 2016" was conducted with the purpose of knowing how the generation of waste, Poor management in the homes of the Parish or inadequate planning by the Municipality, affect the quality of life of the population. The creation of new businesses, cultural changes and the growth of the population has generated that the amount of waste produced is greater; Waste that must be handled correctly, both by the entity in charge of providing the public cleaning service and by the people who generate them. The importance of the research lies in knowing what the existing effects of this problem are and in finding the most viable solutions so that the existing consequences are reduced or eliminated in its totality and the quality of life of the residents improve. From the study it was possible to determine that due to the inadequate management of the residues there are repercussions to the health, food, housing and green areas of the people and that affect their quality of life. The health problems are due to the contaminated foods that when they are ingested they give rise to infections, fevers, diarrhea, etc. Which mainly affect children. In contrast the social problems found are the generation of bad smells and the bad aspect of the home.